Identification of plant growth promoting antagonistic bacteria against Xanthomonas oryzae pv. oryzae in Bangladesh - Islam, Md Rashidul; Islam, Noor-E-Tajkia; Juthy, Papia Sharmin; Haque, Md Mahbubul; Rahman, Md Mahfujur (Fundamental and Applied Agriculture, 2019)
The purpose of this work was to isolate and identify the plant growth promoting bacteria from rice phylloplane and rhizosphere that antagonistic to X. oryzae pv. oryzae. Rice phylloplane and rhizosphere bacteria were isolated from the surface of rice leaves and stem as well as from the soil attached to the roots of rice plants, respectively. The antagonistic activity of these isolated bacteria was determined by dual culture method. The antagonistic bacterial isolates were identified by sequencing of 16SrDNA. The activities related to plant growth promotion were determined by Indole Acetic Acid (IAA) production, siderophore and phosphate solubi- lization assay. The promotion of plant growth was assessed by the deter- mination of root length, shoot length and vigor index. Sixteen bacterial isolates were identified as antagonist to X. oryzae pv. oryzae out of 300 bacterial isolates by dual culture method. The maximum growth inhibition (33.5 mm) of X. oryzae pv. oryzae was recorded in plate inoculated with BDISOB05P while the minimum growth inhibition (5 mm) was recorded by BDISOB98P and BDISOB272R. The moderate growth inhibition was recorded in BDISOB241P, BDISOB16P, BDISOB306R, BDISOB242P, BDISOB220R, BDISOB04P, BDISOB258R, BDISOB219R, BDISOB221R, BDISOB275R, BDISOB283R and BDISOB61R. 16S rDNA sequencing was used to identify the bacterial isolates which were antagonistic. The bacterial iso- lates were identified BDISOB04P as Pseudomonas putida, BDISOB05P as Pseudomonas putida, BDISOB16P as Bacillus sp., BDISOB98P as Stenotrophomonas maltophilia, BDISOB241P as Burkholderia sp., BDISOB242P as Burkholderia gladioli, BDISOB219R as Pseudomonas taiwanensis, BDISOB220R as Serratia sp., BDISOB221R as Pseudomonas sp., BDISOB222R as Pseudomonas plecoglossicida, BDISOB258R as Pseudomonas putida, BDISOB272R as Stenotrophomonas maltophilia, BDISOB275R as Pseudomonas putida, BDISOB283R as Pseudomonas fluorescens and BDISOB306R as P. putida. Eight antagonistic bacterial isolates produce IAA, sixteen bacterial isolates were able to produce siderophore and nine bacterial isolates were found to show phosphate solubilizing capability. The results of plant growth promotion activities indicating that these bacterial isolates can increase the root growth, shoot growth and vigor index.